Reutilización del desecho de PVC como agente estabilizador de sub-bases granulare (2012)
A pavement consists of a set of superimposed layers, relatively horizontal, that are designed and built technically with appropriate materials and properly compacted with the ability to effectively resist efforts repeated traffic loads conveys during the period for which it was designed (Montejo, 2008). Granular materials comprising superimposed layers are not easily found in natural and somehow must be linked with materials artificial achieving these absorb the forces generated by traffic and avoid distortions in the field contributing to the durability of the road. These features make the materials used in the structure meet specifications or standards that ensure the proper functioning granular layer, achieving the desired strength during the design period, in this case meets the granular material is not necessary to apply stabilization techniques for improving soil properties. This research tries to include the part where granular materials are analyzed normally used by applying a mechanical stabilization process when mixed with a percentage of recycled plastic material of PVC derived by half of the graphical method, this mixture will use layered materials subgrades paving purposes, determining the physical and mechanical characteristics of the mixture, as Grit, Atterberg Limits, Resistance (CBR) and durability. In the present study aimed to develop a methodological process for stabilization of granular sub-base using recycled PVC as a stabilizer in percentages. The objectives of this work are: 1. To determine the physical and mechanical properties of granular sub-base 2. Determine the physical - mechanical properties of granular material Type 1 sub-base Paving the purpose of stabilizing a material by mixing plastic product and recycling of waste PVC. 3. To analyze the bearing capacity of granular sub-base 4. To analyze the bearing capacity of the mixture of granular subbase and recycled PVC. 5. Analyze and compare results of different tests applied to the mixture of granular sub-base with recycled PVC with the requirements of the standard INVIAS. By implementing the stabilization of a granular subbase we find that this has a low resistance to withstand the loads imposed by traffic. This is why it is necessary to include a material with appropriate characteristics to improve the properties of the sub-base, in our case the material employee is recycling pvc. By including PVC waste is listed as a durable product that is not affected by humus, corrosive liquids, acidic solutions, basic solutions, saline solutions, solvents and chemicals, and is resistant to attacks produced by the environment, Unlike other stabilizers PVC waterproofing is an advantage because in our sub-base is not present or absorption of moisture infiltrations and go away, the time required for it to be evacuated will be very short. In the development of the project it was determined that the disposal of PVC additive CBR improves a granular sub-base rate from 4% to 6%, in which case keeps the original properties, it was found that by including percentages over 6% of pvc in Sub-density base is lost, because the waste material is lightweight. By replacing certain percentage of the Sub-base material pvc recycling, the structure loses weight, so when making the density experiment, both materials are compacted in a constant volume vessel, and we know that the density is the ratio between weight and volume that it contains, to be constant volume and reduce the weight of the mixture of granular material and for sub-base pvc, the mixture loses density. The granular material mixture analyzed and disposal of PVC, meet strength requirements required by the standard pavements Invias that is the standard that governs our country besides this provides a support surface granular base or concrete slab and lightens the weight to be borne by the subgrade, besides all these advantages exist in economic savings because the amount of granular material for sub-base would be lower, as a percentage of this will be replaced.